A Unique Simulation Methodology for Practicing Clinical Decision Making - Shimon Amar; Yuval Bitan (Journal of Medical Education and Curricular Development)
BACKGROUND While bedside teaching offers invaluable clinical experience, its availability is limited. Challenges such as a shortage of clinical placements and qualified teaching physicians, coupled with increasing medical student numbers, exacerbate this issue. Simulation-based learning encompasses varied educational values and has the potential to serve as an important tool in medical students’ education. OBJECTIVES In this study, we evaluate a new Clinical Decision Making Integrated Digital Simulation (CDMIDS) method that was developed in order to enhance the clinical decision-making competency and self-confidence of medical students early in their clinical training through practicing fundamental core skills. METHODS The study compares 108 4th-year medical students’ questionnaire responses pre-/postself-assessments following practice of a new clinical decision-making simulation methodology. RESULTS Results indicate a positive participant experience, with the simulation perceived as a valuable platform for practicing integrated bedside decision making. Notably, participants demonstrated a statistically significant increase in willingness to make clinical decisions. The simulation contributed to enhanced knowledge, professional skills, and self-confidence in clinical decision making. CONCLUSION The use of a CDMIDS method integrates clinical decision making as part of early medical school curriculum. Moreover, the method boosts learners’ professional confidence, self-directed learning, and additional experiences. The method is flexible and can be applied in any medical school, especially those with limited resources, by making specific, localized modifications.